Penerapan Metode Pembelajaran STAD (Student Teams Achivement Division) dalam Pembelajaran Biologi untuk Meningkatkan Minat, Keaktifan Serta pada Hasil Belajar Siswa di SMA Negeri 1 Ciomas Serang Banten: Penelitian - Ani Nikmah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Application of the STAD Learning Model in Biology Learning to Increase Interest, Activeness and Learning Outcomes of Ciomas 1 Public High School Students in Biology Subjects. This research was conducted to see students' ability to understand biology lessons and to determine their level of interest, activity and learning outcomes using the method used, namely STAD (Student Team Achivement Division). The research subjects in this case were 40 students consisting of 21 men and 19 women. In this research, of course, the results were in accordance with what the researchers expected, namely that in the pre-cycle students tended to be passive or silent, the learning process was carried out conventionally and did not use the STAD method, in cycle 1 students began to show activeness in learning, and the post test results were 78.63, then in cycle II the results increased by 89.12, in cycle II students were much more active, responsive so that the results of the interest questionnaire also increased, from initially 57.5 in cycle I to 80.62 in cycle II.